2023
DOI: 10.1021/acs.jctc.2c01255
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Overfitting the van der Waals Radii of Ions

Abstract: Atomic radii play important roles in scientific research. The covalent radii of atoms, ionic radii of ions, and van der Waals (VDW) radii of neutral atoms can all be derived from crystal structures. However, the VDW radii of ions are a challenge to determine because the atomic distances in crystal structures were determined by a combination of VDW interactions and electrostatic interactions, making it unclear how to define the VDW sphere of ions in such an environment. In the present study, we found that VDW r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…The results from this study show that two histidine residues contributing to the metal coordination sites lose their interactions with the metal ion. Two oxygen atoms from the negatively charged residues in the binding site then take over and coordinate with the metal ion in a bidentate mode.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The results from this study show that two histidine residues contributing to the metal coordination sites lose their interactions with the metal ion. Two oxygen atoms from the negatively charged residues in the binding site then take over and coordinate with the metal ion in a bidentate mode.…”
Section: Resultsmentioning
confidence: 77%
“…To assess our parameters beyond a system composed exclusively of acetate and a metal ion, we applied them to a system containing the Escherichia coli Glyoxalase I metalloprotein (PDB ID: 1F9Z). A previous study on this protein indicates that the z12–6 parameters fail to maintain the coordination modes of both Ni­(II) binding sites after 80 ns of MD simulations . This metalloprotein is a homodimer comprising two metal-binding sites, with each binding site including His5, His74, Glu122, and Glu56 and two water molecules coordinating with one nickel (see Figure ).…”
Section: Resultsmentioning
confidence: 87%
“…Conversely, Jungwirth and co-workers modified the description of the electrostatic term by exploiting an additional charge-scaling term . Finally, Schwierz and colleagues have introduced long-range interaction potential and optimized Lorentz combination rules. , Nevertheless, it remains questionable the generalizability and transferability of nonbonded 12–6 Mg 2+ models to RNA systems …”
Section: Computational Methods For Predicting Non-coding Rna–disease ...mentioning
confidence: 99%
“…Li’s methodology was a significant breakthrough because it provided a method for accurately simulating the behavior of a wide range of cations across the periodic table, including those with charges of +1, , + 2, , +3, and +4. , The comparison of the structural properties, namely the Ln 3+ first coordination shell, and hydration free energies (HFEs) with experimental Marcus’ values is crucial in determining the accuracy of this approach. This thorough investigation demonstrated that Li’s approach yielded excellent results for a wide range of cations while significantly reducing the computational overhead associated with polarization calculations . Such an approach has already been used for refining previous force fields of mono-atomic cations in interaction with nucleic acids, proteins, and imidazole .…”
Section: Introductionmentioning
confidence: 91%